The effects of family support on women entrepreneurs' well-being in the Arab region: A theoretical investigation and future research agenda - Haneen Attaallah (New Applied Studies in Management, Economics & Accounting)
The paper presents a theoretical investigation exploring the effects of the types of family support on the subjective well-being of entrepreneurial women in the Arab region. Despite the increasing acknowledgment of the significance of women's entrepreneurship in driving economic development, there remains a limited understanding of the roles played by different types of family support and their effects on the well-being of women entrepreneurs within the Arab states. Drawing on existing literature and theoretical frameworks, we argue that family support (instrumental, financial, and emotional) is crucial in facilitating the entrepreneurial endeavors and subjective well-being of women entrepreneurs operating in Arab states, where patriarchal forces and discriminatory social norms often shape the entrepreneurial landscape. Furthermore, this paper outlines a future research agenda to bridge the knowledge gap on this issue. We emphasize the importance of considering cultural and contextual factors while exploring the dynamics of family support and its outcomes and conducting empirical investigations in the Arab region. Overall, this paper contributes to understanding the unique challenges and opportunities faced by women entrepreneurs in the Arab region and can inform policymakers, support organizations, and stakeholders in designing effective interventions and support mechanisms for women entrepreneurs in the Arab states.